Mitochondrial metabolism coordinates stage-specific repair processes in macrophages during wound healing - Willenborg, Sebastian; Sanin, David E.; Jais, Alexander; Ding, Xiaolei; Ulas, Thomas; Nüchel, Julian; Popović, Milica; MacVicar, Thomas; Langer, Thomas; Schultze, Joachim L.; Gerbaulet, Alexander; Roers, Axel; et al. (Cell metabolism, 2021)
Wound healing is a coordinated process that initially relies on pro-inflammatory macrophages, followed by a pro-resolution function of these cells. Changes in cellular metabolism likely dictate these distinct activities, but the nature of these changes has been unclear. Here, we profiled early- versus late-stage skin wound macrophages in mice at both the transcriptional and functional levels. We found that glycolytic metabolism in the early phase is not sufficient to ensure productive repair. Instead, by combining conditional disruption of the electron transport chain with deletion of mitochondrial aspartyl-tRNA synthetase, followed by single-cell sequencing analysis, we found that a subpopulation of early-stage wound macrophages are marked by mitochondrial ROS (mtROS) production and HIF1α stabilization, which ultimately drives a pro-angiogenic program essential for timely healing. In contrast, late-phase, pro-resolving wound macrophages are marked by IL-4Rα-mediated mitochondrial respiration and mitohormesis. Collectively, we identify changes in mitochondrial metabolism as a critical control mechanism for macrophage effector functions during wound healing. [Display omitted] •Early-stage, inflammatory versus late-stage, pro-resolving wound macrophages are profiled•Pro-inflammatory wound macrophages are marked by mtROS production and HIF1α stabilization•This molecular process is required for proper vascularization during wound repair•Pro-resolving macrophages are marked by mitochondrial respiration and mitohormesis How mitochondrial metabolism contributes to the early-stage, pro-inflammatory versus late-stage, pro-resolution functions of macrophages during wound healing requires further investigation. Here, Willenborg et al. show that effective wound healing requires the production of mtROS in early-stage wound macrophages to promote proper vascularization, while late-stage wound macrophages are dependent on OXPHOS and mitohormesis.